High-energy-density lithium ion battery positive electrode and preparation method thereof
By adopting a composite liquid collector design in the positive electrode of the lithium-ion battery, using an aluminum foil layer and a gradient-distributed composite foam aluminum layer, the problem of insufficient mechanical strength and structural stability when the current collector is improved in detail and conductivity is achieved, and a high degree of Energy density, rate performance and long cycle life effects.
Patent Information
- Application Number
- CN202411466994.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-10-21
AI Technical Summary
When the positive current collector of existing lithium-ion batteries improves the specific surface area and conductivity, it is difficult to take into account both mechanical strength and structural stability, and is prone to deformation or fracture, affecting battery performance and cycle life.
The composite fluid-collection design is adopted, which includes an aluminum foil layer and a composite foam aluminum layer composed of three layers of foam aluminum of different densities, porosity and thickness. Through gradient density, porosity and thickness distribution, it achieves high specific surface area and high conductivity. A balance between high mechanical strength and high structural stability.
The energy density, rate performance and cycle life of the positive electrode of the lithium-ion battery are significantly improved, local deformation and fracture of the current collector are avoided, and the mechanical stability and reliability of the battery are enhanced.
Smart Images

Figure CN119447316A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a lithium ion battery positive electrode with high energy density and a preparation method thereof. Background Art
[0002] Lithium-ion batteries have been widely used in portable electronic devices, electric vehicles, energy storage systems and other fields due to their high energy density, long cycle life and environmental friendliness. However, with the continuous expansion of application fields and the increasing performance requirements, the existing lithium-ion battery cathode materials and structural designs can no longer meet the requirements of high energy density, high rate performance and long cycle stability.
[0003] In the positive electrode of lithium-ion batteries, the current collector acts as a carrier of active materials and an electron transport channel. Its performance has an important impact on the energy density, rate performance and cycle stability of the battery. At present, aluminum foil is commonly used as the current collector material for commercial lithium-ion battery positive electrodes. However, the aluminum foil current collector has problems such as low specific surface area and limited active material loading, making it difficult to further improve the energy density of the battery. In order to solve this problem, the researchers proposed a design scheme using foamed aluminum as the positive electrode current collector.
[0004] However, the existing aluminum foam current collector generally adopts a single-layer uniform porosity and density design, which often sacrifices the mechanical strength and structural stability of the current collector while improving the specific surface area and conductivity. It is easy to deform or break during battery assembly and charging and discharging, resulting in problems such as active material shedding and increased interface impedance, which seriously affects the performance and cycle life of the battery. In addition, the stress distribution of the single-layer aluminum foam current collector is uneven, and it is easy to be damaged in the stress concentration area, further reducing the mechanical stability and reliability of the current collector.
[0005] Therefore, how to design and prepare a current collector with high specific surface area, high conductivity, high mechanical strength and high structural stability, and then develop a lithium-ion battery positive electrode with high energy density, high rate performance and long cycle life, is still a technical problem that needs to be urgently solved in this field. Summary of the invention
[0006] The main purpose of the present invention is to provide a lithium ion battery positive electrode current collector with high specific surface area, high conductivity, high mechanical strength and high structural stability to effectively improve the energy density, rate performance and cycle performance of the lithium ion battery positive electrode.
[0007] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0008] A high energy density lithium ion battery positive electrode, comprising a composite current collector and a positive electrode active material coating coated on at least one surface of the composite current collector, wherein the composite current collector comprises an aluminum foil layer and a composite foam aluminum layer disposed on the aluminum foil layer, wherein the composite foam aluminum layer is composed of three layers of foam aluminum with different densities, different porosities and different thicknesses;
[0009] The composite foam aluminum layer includes a first foam aluminum, a second foam aluminum and a third foam aluminum which are arranged in sequence from the inside to the outside, and the density ρ1 of the first foam aluminum, the density ρ2 of the second foam aluminum and the density ρ3 of the third foam aluminum satisfy the relationship: ρ1>ρ2>ρ3; the porosity φ1 of the first foam aluminum, the porosity φ2 of the second foam aluminum and the porosity φ3 of the third foam aluminum satisfy the relationship: φ1<φ2<φ3; and the thickness h1 of the first foam aluminum, the thickness h2 of the second foam aluminum and the thickness h3 of the third foam aluminum satisfy the relationship: h1<h2<h3.
[0010] Preferably, the density ρ1 of the first foamed aluminum is 0.5-0.9 g / cm³, the density ρ2 of the second foamed aluminum is 0.3-0.5 g / cm³, and the density ρ3 of the third foamed aluminum is 0.1-0.3 g / cm³.
[0011] Preferably, the porosity φ1 of the first foamed aluminum is 50-70%, the porosity φ2 of the second foamed aluminum is 70-85%, and the porosity φ3 of the third foamed aluminum is 85-95%.
[0012] Preferably, the thickness h1 of the first aluminum foam is 0.5-1 μm, the thickness h2 of the second aluminum foam is 1-2 μm, the thickness h3 of the third aluminum foam is 2-4 μm; the thickness h4 of the aluminum foil layer is 0.5-1 μm; and the total thickness of the composite current collector is 4-8 μm.
[0013] Preferably, the surface of the composite foam aluminum layer is further provided with a carbon nano coating, and the thickness of the carbon nano coating is 10-20 nm.
[0014] Preferably, the pore size d1 of the first foam aluminum, the pore size d2 of the second foam aluminum, and the pore size d3 of the third foam aluminum satisfy the relationship: d1<d2<d3.
[0015] Preferably, the pore size d1 of the first foam aluminum is 1-5 μm, the pore size d2 of the second foam aluminum is 5-10 μm, and the pore size d3 of the third foam aluminum is 10-15 μm.
[0016] In addition, the present invention also provides a method for preparing the above-mentioned high energy density lithium ion battery positive electrode, comprising the following steps:
[0017] 1) preparing a first aluminum foam layer slurry, a second aluminum foam layer slurry and a third aluminum foam layer slurry respectively;
[0018] The first foam aluminum layer slurry is made by mixing aluminum powder, urea and polyvinyl pyrrolidone in a mass ratio of 100:(15-25):1, adding anhydrous ethanol, and adjusting the solid content to 30-50wt%;
[0019] The second foam aluminum layer slurry is made by mixing aluminum powder, urea and polyvinyl pyrrolidone in a mass ratio of 100:(25-35):1, adding anhydrous ethanol, and adjusting the solid content to 15-30wt%;
[0020] The third foam aluminum layer slurry is made by mixing aluminum powder, urea and polyvinyl pyrrolidone in a mass ratio of 100: (45-55): 1, adding anhydrous ethanol, and adjusting the solid content to 5-15wt%;
[0021] 2) preheating the aluminum foil substrate, and then coating the first aluminum foam layer slurry, the second aluminum foam layer slurry and the third aluminum foam layer slurry on the aluminum foil substrate in sequence, and spraying a small amount of anhydrous ethanol on the surface of each layer of slurry during the coating process;
[0022] 3) Place the coated aluminum foil in a vacuum sintering furnace, and under the protection of argon or nitrogen, heat it to 650-750℃ at a heating rate of 2-5℃ / min, and keep it warm for 0.5-1h to sinter the aluminum powder to form a gradient porous structure. At the same time, urea decomposes to produce gas to form a gradient aluminum foam layer;
[0023] 4) After cooling, the composite current collector is obtained, and the composite current collector is ultrasonically cleaned in anhydrous ethanol for 3-5 minutes to remove the urea decomposition products and impurities remaining on the surface, and then the composite current collector is dried;
[0024] 5) coating the positive electrode active material coating slurry on at least one surface of the composite current collector and drying it to obtain the positive electrode of the lithium ion battery.
[0025] Preferably, step 4) further comprises surface modification of the composite current collector obtained after cooling, depositing a 10-20 nm thick carbon nanocoating, and hot rolling the surface modified composite current collector on a precision rolling mill at a rolling temperature of 100-150° C. and a rolling rate of 5-10%.
[0026] Preferably, in step 1), in the first aluminum foam layer slurry, the particle size of the aluminum powder is 0.1~0.4μm, and the particle size of the urea is 0.2~0.5μm; in the second aluminum foam layer slurry, the particle size of the aluminum powder is 0.2~0.8μm, and the particle size of the urea is 0.4~1μm; in the third aluminum foam layer slurry, the particle size of the aluminum powder is 0.5~1.5μm, and the particle size of the urea is 0.8~1.8μm.
[0027] Compared with the prior art, the present invention has at least the following beneficial effects:
[0028] 1) The positive electrode of the present invention adopts a composite current collector of aluminum foil and composite foam aluminum, wherein the composite foam aluminum layer has a high specific surface area and a three-dimensional network structure, which is not only conducive to the infiltration of the electrolyte, but also can load more active materials and is conducive to the uniform distribution of the active materials, which can shorten the transmission path of electrons and ions, reduce the interface resistance, and improve the energy density and rate performance of the battery.
[0029] 2) The composite foam aluminum with gradient density, porosity and thickness distribution used in the present invention can achieve layer-by-layer transmission and buffering of stress, avoid stress concentration leading to local deformation, fracture or damage of the current collector, and improve the mechanical stability and reliability of the current collector.
[0030] 3) The composite foam aluminum with gradient density, porosity and thickness distribution used in the present invention can not only significantly improve the specific surface area and conductivity of the current collector, but also take into account the mechanical strength and structural stability, effectively solving the problem that the existing single-layer foam aluminum current collector is prone to deformation and fracture.
[0031] 4) Among them, the second and third layers of low-density and high-porosity aluminum foam can provide a larger specific surface area, which is conducive to the loading of active materials and the infiltration of electrolytes, thereby improving the energy density and rate performance of the battery; while the first layer of aluminum foam has a relatively high density and low porosity, which can provide sufficient mechanical support and anti-deformation ability to ensure the structural integrity and stability of the composite current collector. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 is a schematic structural diagram of a positive electrode in one embodiment of the present invention;
[0033] Figure 2 Schematic diagram of the structure of a composite current collector of a positive electrode in one embodiment of the present invention;
[0034] Figure 3 Schematic diagram of the structure of a composite current collector of a positive electrode in another embodiment of the present invention.
[0035] In the figure: 1. composite current collector; 11. aluminum foil layer; 12. composite foam aluminum layer; 121. first foam aluminum; 122. second foam aluminum; 123. third foam aluminum; 13. carbon nanocoating; 2. positive electrode active material coating. DETAILED DESCRIPTION
[0036] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] Please see attached Figure 1~2 The present invention provides a high energy density lithium ion battery positive electrode, comprising a composite current collector 1 and a positive electrode active material coating 2 coated on at least one surface of the composite current collector 1, the composite current collector 1 comprising an aluminum foil layer 11 and a composite foam aluminum layer 12 arranged on the aluminum foil layer 11, the composite foam aluminum layer 12 is composed of three layers of foam aluminum with different densities, different porosities and different thicknesses; the composite current collector 1 is connected with a positive electrode tab;
[0038] The composite foam aluminum layer 12 includes a first foam aluminum 121, a second foam aluminum 122 and a third foam aluminum 123 which are arranged in sequence from the inside to the outside. The density ρ1 of the first foam aluminum 121, the density ρ2 of the second foam aluminum 122 and the density ρ3 of the third foam aluminum 123 satisfy the relationship: ρ1>ρ2>ρ3; the porosity φ1 of the first foam aluminum 121, the porosity φ2 of the second foam aluminum 122 and the porosity φ3 of the third foam aluminum 123 satisfy the relationship: φ1<φ2<φ3; and the thickness h1 of the first foam aluminum 121, the thickness h2 of the second foam aluminum 122 and the thickness h3 of the third foam aluminum 123 satisfy the relationship: h1<h2<h3.
[0039] The composite current collector 1 of the present invention comprises an aluminum foil layer 11 and a composite aluminum foam layer 12, wherein the composite aluminum foam layer 12 is composed of three layers of aluminum foams with different densities, porosities and thicknesses, which are distributed in a gradient manner. This structure has the following outstanding advantages:
[0040] 1) High specific surface area: The gradient-distributed composite aluminum foam layer 12 has a high specific surface area and a three-dimensional porous structure as a whole. The outer layer of low-density, high-porosity and thicker aluminum foam can load more active substances, improve the utilization rate of active materials, and increase battery capacity.
[0041] 2) High conductivity: The outer layer of aluminum foam is in direct contact with the active material, and its loose and porous structure is conducive to the infiltration of the electrolyte and the rapid transmission of ions, thereby reducing the interface resistance; the inner layer of aluminum foam with high density and low porosity can provide an effective electron transmission channel, ensuring the high conductivity of the current collector.
[0042] 3) High mechanical strength: The inner layer of high-density, low-porosity and thin aluminum foam can provide sufficient mechanical support to ensure the structural integrity of the current collector; the middle layer has moderate density and porosity, which plays a transition and buffering role and improves the mechanical stability of the current collector.
[0043] 4) High structural stability: The gradient structure design can achieve layer-by-layer transmission and uniform distribution of stress. The outer layer of low-density, high-porosity and thick aluminum foam can effectively absorb and buffer the stress generated during the battery charging and discharging process, avoid stress concentration leading to local deformation or fracture of the current collector, and extend the cycle life of the battery.
[0044] In summary, the high energy density lithium ion battery positive electrode provided by the present invention adopts an innovative composite current collector 1 design, and achieves a perfect balance of high specific surface area, high conductivity, high mechanical strength and high structural stability through gradient density, porosity, thickness and pore size distribution, which can significantly improve the energy density, rate performance and cycle life of lithium ion batteries.
[0045] In one embodiment of the present application, the density ρ1 of the first aluminum foam 121 is 0.5-0.9 g / cm³, the density ρ2 of the second aluminum foam 122 is 0.3-0.5 g / cm³, and the density ρ3 of the third aluminum foam 123 is 0.1-0.3 g / cm³. While ensuring high specific surface area and high conductivity, mechanical strength and structural stability can be taken into account to obtain a composite aluminum foam current collector with optimal performance.
[0046] In one embodiment of the present application, the porosity φ1 of the first aluminum foam 121 is 50-70%, the porosity φ2 of the second aluminum foam 122 is 70-85%, and the porosity φ3 of the third aluminum foam 123 is 85-95%. While ensuring high specific surface area and high conductivity, mechanical strength and structural stability can be taken into account to obtain a composite aluminum foam current collector with optimal performance.
[0047] In one embodiment of the present application, the thickness h1 of the first aluminum foam 121 is 0.5-1 μm, the thickness h2 of the second aluminum foam 122 is 1-2 μm, and the thickness h3 of the third aluminum foam 123 is 2-4 μm; the thickness h4 of the aluminum foil layer 11 is 0.5-1 μm; and the total thickness of the composite current collector 1 is 4-8 μm. While ensuring high specific surface area and high conductivity, mechanical strength and structural stability can be taken into account to obtain a composite aluminum foam current collector with optimal performance. In addition, the total thickness of the positive electrode composite current collector 1 of the present invention is controlled within the ultra-thin range of 4-8 μm. Compared with the traditional aluminum foil current collector, the thickness and mass of the current collector can be significantly reduced, and the energy density and specific power of the battery can be further improved, which is conducive to the miniaturization and lightweight design of the battery. In addition, the thickness of each aluminum foam layer will also directly affect the performance of the battery; if the thickness of each aluminum foam layer is insufficient, the active material particles may be squeezed out of the pores or destroyed under pressure, which will reduce the overall performance of the pole piece, resulting in a decrease in the rate performance and cycle life of the battery; on the other hand, if the thickness of each aluminum foam layer is too large, the proportion of inactive materials will increase, thereby reducing the energy density of the battery. Therefore, controlling the appropriate thickness of each aluminum foam layer is crucial to optimizing the performance of lithium-ion batteries.
[0048] In one embodiment of the present application, a carbon nano coating 13 is further provided on the surface of the composite foam aluminum layer 12, and the thickness of the carbon nano coating 13 is 10-20 nm. The conductivity and corrosion resistance of the current collector can be further improved, while the interface compatibility between the current collector and the active material is improved and the interface impedance is reduced. The appropriate thickness of the carbon nano coating 13 can avoid pore blockage or increased interface impedance caused by excessive thickness of the coating.
[0049] In one embodiment of the present application, the pore size d1 of the first aluminum foam 121, the pore size d2 of the second aluminum foam 122, and the pore size d3 of the third aluminum foam 123 satisfy the relationship: d1<d2<d3. The pore size gradient distribution is trumpet-shaped to form a multi-level porous structure that is conducive to the diffusion of lithium ions and the embedding of active substances. The large pore size of the outer layer is conducive to the rapid transmission of electrolyte and lithium ions, and the small pore size of the inner layer can inhibit the volume expansion of the active substance, maintain the stability of the electrode structure, and improve the rate performance and cycle stability of the battery.
[0050] In one embodiment of the present application, the pore size d1 of the first aluminum foam 121 is 1-5 μm, the pore size d2 of the second aluminum foam 122 is 5-10 μm, and the pore size d3 of the third aluminum foam 123 is 10-15 μm. It is possible to obtain a composite aluminum foam current collector with optimal performance while ensuring high specific surface area and high conductivity, taking into account mechanical strength and structural stability; and the gradient pore structure is conducive to the uniform distribution and rapid penetration of the electrolyte, improving the ion transmission efficiency of the battery. In addition, the size of the pore size has a decisive influence on the permeability of the slurry; if the pore size is too small, due to the effect of the surface tension of the slurry, the slurry may not be able to effectively fill the pores, which will hinder the uniform distribution of the active material and affect the performance of the pole piece; on the contrary, if the pore size is too large, the slurry will easily overfill the pores, resulting in an increase in the surface density. During the drying process, this overfilling may cause the generation of local cracks, further affecting the rate performance of the battery. Therefore, choosing a suitable pore size is crucial to ensuring the quality of the pole piece and the performance of the battery.
[0051] In addition, the present invention also provides a method for preparing the above-mentioned high energy density lithium ion battery positive electrode, comprising the following steps:
[0052] 1) preparing a first aluminum foam layer slurry, a second aluminum foam layer slurry and a third aluminum foam layer slurry respectively;
[0053] The first foam aluminum layer slurry is made by mixing aluminum powder, urea and polyvinyl pyrrolidone in a mass ratio of 100:(15-25):1, adding anhydrous ethanol, and adjusting the solid content to 30-50wt%;
[0054] The second foam aluminum layer slurry is made by mixing aluminum powder, urea and polyvinyl pyrrolidone in a mass ratio of 100:(25-35):1, adding anhydrous ethanol, and adjusting the solid content to 15-30wt%;
[0055] The third foam aluminum layer slurry is made by mixing aluminum powder, urea and polyvinyl pyrrolidone in a mass ratio of 100: (45-55): 1, adding anhydrous ethanol, and adjusting the solid content to 5-15wt%;
[0056] 2) Preheating the aluminum foil substrate, and then coating the first aluminum foam layer slurry, the second aluminum foam layer slurry and the third aluminum foam layer slurry on the aluminum foil substrate in sequence. During the coating process, spray a small amount of anhydrous ethanol on the surface of each layer of slurry to promote the bonding and fusion between the layers;
[0057] 3) Place the coated aluminum foil in a vacuum sintering furnace, and under the protection of argon or nitrogen, heat it to 650-750℃ at a heating rate of 2-5℃ / min, and keep it warm for 0.5-1h to sinter the aluminum powder to form a gradient porous structure. At the same time, urea decomposes to produce gas to form a gradient aluminum foam layer;
[0058] 4) After cooling, the composite current collector 1 is obtained, and the composite current collector 1 is ultrasonically cleaned in anhydrous ethanol for 3-5 minutes to remove urea decomposition products and impurities remaining on the surface, and then the composite current collector 1 is dried;
[0059] 5) The positive electrode active material coating slurry is coated on at least one surface of the composite current collector 1 and dried to obtain a positive electrode for a lithium-ion battery.
[0060] The present invention provides a composite aluminum foam current collector and a method for preparing a positive electrode of a lithium-ion battery, which adopts a process route of gradient slurry ratio and layer-by-layer coating and sintering, and is simple to operate and easy to control. By adjusting the slurry components, solid content and coating process parameters, the microstructure parameters such as density, porosity, thickness and pore size of the composite aluminum foam can be accurately controlled to ensure the consistency and repeatability of the current collector performance. In addition, the raw materials and equipment used in the present invention are conventional and easily available, which can reduce production costs and has good industrialization prospects.
[0061] In one embodiment of the present application, step 4) further includes surface modification of the composite current collector 1 obtained after cooling, depositing a 10-20 nm thick carbon nano coating 13, and hot rolling the surface modified composite current collector 1 on a precision rolling mill, with a rolling temperature of 100-150°C and a rolling rate of 5-10%. The introduction of surface modification and hot rolling processes can further improve the conductivity and bonding strength of the composite current collector 1, and improve the interface compatibility and mechanical properties between the current collector and the active material coating.
[0062] In one embodiment of the present application, in step 1), in the first aluminum foam layer slurry, the particle size of the aluminum powder is 0.1-0.4 μm, and the particle size of the urea is 0.2-0.5 μm; in the second aluminum foam layer slurry, the particle size of the aluminum powder is 0.2-0.8 μm, and the particle size of the urea is 0.4-1 μm; in the third aluminum foam layer slurry, the particle size of the aluminum powder is 0.5-1.5 μm, and the particle size of the urea is 0.8-1.8 μm. The particle sizes of the aluminum powder and the urea pore former in different layers of slurry are preferably selected to effectively control the pore size and porosity of the aluminum foam, ensure the formation of a gradient structure, and avoid problems such as incomplete sintering or pore collapse caused by excessively large or small particle sizes.
[0063] In one embodiment of the present application, the positive electrode active material coating 2 includes a positive electrode active substance, a binder and a conductive agent, wherein the types and amounts of the positive electrode active substance, the binder and the conductive agent in the positive electrode active material coating 2, as well as the thickness of the positive electrode active material coating 2, etc. can all be conventional choices in the art. For example, as some specific examples, the positive electrode active substance in the positive electrode active material coating 2 may include but is not limited to lithium cobalt oxide, lithium manganese oxide, lithium nickel cobalt manganese oxide, lithium iron phosphate, etc., the binder may include but is not limited to polyvinylidene fluoride, styrene butadiene rubber, polyvinyl alcohol, polyurethane, etc., and the conductive agent may include but is not limited to carbon nanofibers, carbon nanotubes, conductive carbon black, graphene, etc. The surface density of the positive electrode active material coating 2 can be 10 to 12 mg / cm 2 .
[0064] In one embodiment of the present application, the positive electrode active material coating 2 also includes 1,3,5-tri(4-carboxyphenyl)benzene. By adding 1,3,5-tri(4-carboxyphenyl)benzene to the positive electrode active material coating, it can form coordination bonds with the active substance in the pores of the foamed aluminum to achieve connectivity of the internal structure, which is beneficial to improving the conductive performance, strengthening the internal support structure of the foamed aluminum, and enhancing the bending resistance of the positive electrode sheet. At the same time, the binding effect of 1,3,5-tri(4-carboxyphenyl)benzene on the active substance can also reduce the generation of free active substances during the use of the battery and improve the battery cycle performance.
[0065] Specifically, adding 1,3,5-tris(4-carboxyphenyl)benzene to the positive electrode active material coating has at least the following advantages:
[0066] 1) The center of 1,3,5-tri(4-carboxyphenyl)benzene is a benzene ring, and three 4-carboxyphenyl groups are uniformly modified at the 1,3,5 positions of the central benzene ring. This symmetrical three-dimensional spatial structure is conducive to the formation of a uniform and stable metal organic framework; the three-dimensional structure of 1,3,5-tri(4-carboxyphenyl)benzene can provide more coordination sites and steric hindrance, forming a more three-dimensional cross-linked network and enhancing the internal support of aluminum foam. 2) 1,3,5-tri(4-carboxyphenyl)benzene contains three free carboxyl groups, which can form coordination bonds with the central ions of multiple positive active materials (such as transition metal oxides); each 1,3,5-tri(4-carboxyphenyl)benzene molecule can connect three active material particles to form a "Y" type coordination structure; this multi-coordination site design can increase the connectivity of active materials, promote electron and ion transmission, and improve conductivity.
[0067] 3) The three 4-carboxyphenyl groups of 1,3,5-tri(4-carboxyphenyl)benzene present a unique spatial orientation. After forming a metal-organic framework, they can form a staggered three-dimensional barrier structure in the pores of foamed aluminum. On the one hand, this spatial steric hindrance effect can increase the mechanical strength of the positive electrode material and improve its bending resistance. On the other hand, it can also effectively inhibit the shedding and dissolution of active substances during the battery cycle, reduce the generation of free active substances, and improve the cycle stability of the battery.
[0068] 4) The central benzene ring of 1,3,5-tri(4-carboxyphenyl)benzene and the three 4-carboxyphenyl groups are connected by rigid σ bonds, and the entire molecular conformation is relatively stable; this rigid structure is conducive to maintaining the structural integrity of the metal organic framework in the complex and porous internal environment of aluminum foam, and avoiding the collapse of the framework caused by the change of ligand conformation; at the same time, the rigid structure can also buffer the volume change during the battery charging and discharging process, and maintain the structural stability of the positive electrode material. 5) In addition, the benzene ring structure in 1,3,5-tri(4-carboxyphenyl)benzene has good chemical stability and electrochemical stability; within the potential window of battery operation, 1,3,5-tri(4-carboxyphenyl)benzene will not undergo redox reactions, nor will it have side reactions with the electrolyte; this stable electrochemical behavior can ensure that 1,3,5-tri(4-carboxyphenyl)benzene always plays a role of coordination connection in long-term cycles, maintain the structural integrity and conductive network of the positive electrode material, and extend the service life of the battery.
[0069] The embodiments of the present application are described in detail below. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. The reagents or instruments used without indicating the manufacturer are all conventional products that can be obtained commercially.
[0070] Example 1
[0071] Preparation of positive electrode:
[0072] The positive electrode of the lithium-ion battery of this embodiment includes a composite current collector 1 and a positive electrode active material coating 2 coated on a surface of the composite current collector 1. The composite current collector 1 includes an aluminum foil layer 11 and a composite foam aluminum layer 12 arranged on the aluminum foil layer 11. The composite foam aluminum layer 12 is composed of three layers of foam aluminum with different densities, different porosities and different thicknesses. The composite current collector 1 is connected to a positive electrode tab.
[0073] The composite foam aluminum layer 12 includes a first foam aluminum 121, a second foam aluminum 122 and a third foam aluminum 123 which are arranged in sequence from the inside to the outside. The density ρ1 of the first foam aluminum 121, the density ρ2 of the second foam aluminum 122 and the density ρ3 of the third foam aluminum 123 satisfy the relationship: ρ1>ρ2>ρ3; the porosity φ1 of the first foam aluminum 121, the porosity φ2 of the second foam aluminum 122 and the porosity φ3 of the third foam aluminum 123 satisfy the relationship: φ1<φ2<φ3; and the thickness h1 of the first foam aluminum 121, the thickness h2 of the second foam aluminum 122 and the thickness h3 of the third foam aluminum 123 satisfy the relationship: h1<h2<h3.
[0074] Specifically, in this embodiment, the density ρ1 of the first aluminum foam 121 is 0.7g / cm³, the density ρ2 of the second aluminum foam 122 is 0.4g / cm³, and the density ρ3 of the third aluminum foam 123 is 0.2g / cm³. The porosity φ1 of the first aluminum foam 121 is 60%, the porosity φ2 of the second aluminum foam 122 is 80%, and the porosity φ3 of the third aluminum foam 123 is 90%. The thickness h1 of the first aluminum foam 121 is 0.5μm, the thickness h2 of the second aluminum foam 122 is 1.5μm, and the thickness h3 of the third aluminum foam 123 is 3μm; the thickness h4 of the aluminum foil layer 11 is 1μm; the total thickness of the composite current collector 1 is 6μm.
[0075] The preparation method of the positive electrode sheet is as follows:
[0076] 1) preparing a first aluminum foam layer slurry, a second aluminum foam layer slurry and a third aluminum foam layer slurry respectively;
[0077] The first foam aluminum layer slurry is made by mixing aluminum powder, urea and polyvinyl pyrrolidone in a mass ratio of 100:20:1, adding anhydrous ethanol, and adjusting the solid content to 40wt%;
[0078] The second foam aluminum layer slurry is made by mixing aluminum powder, urea and polyvinyl pyrrolidone in a mass ratio of 100:30:1, adding anhydrous ethanol, and adjusting the solid content to 25wt%;
[0079] The third foam aluminum layer slurry is made by mixing aluminum powder, urea and polyvinyl pyrrolidone in a mass ratio of 100:50:1, adding anhydrous ethanol, and adjusting the solid content to 10wt%;
[0080] 2) Preheating the aluminum foil substrate, and then coating the first aluminum foam layer slurry, the second aluminum foam layer slurry and the third aluminum foam layer slurry on the aluminum foil substrate in sequence. During the coating process, spray a small amount of anhydrous ethanol on the surface of each layer of slurry to promote the bonding and fusion between the layers;
[0081] 3) Place the coated aluminum foil in a vacuum sintering furnace, and under the protection of argon atmosphere, heat it to 700°C at a heating rate of 4°C / min and keep it at that temperature for 1 hour, so that the aluminum powder is sintered to form a gradient porous structure. At the same time, urea decomposes to produce gas to form a gradient aluminum foam layer.
[0082] 4) After cooling, the composite current collector is obtained, and the composite current collector is ultrasonically cleaned in anhydrous ethanol for 3-5 minutes to remove the urea decomposition products and impurities remaining on the surface, and then the composite current collector is dried at a temperature of 70°C for 0.5 hours;
[0083] 5) The positive electrode active material lithium nickel cobalt manganese oxide, the conductive agent conductive carbon black, and the binder polyvinylidene fluoride are dispersed in the solvent NMP (N-methylpyrrolidone) in a mass ratio of 95:2:3, and the positive electrode active material coating slurry is obtained after stirring evenly, and coated on the surface of the composite current collector, and dried to obtain the positive electrode sheet of the lithium ion battery.
[0084] Preparation of negative electrode sheet:
[0085] Hard carbon, carbon black and aqueous carboxymethyl cellulose are dispersed in water at a mass ratio of 95:2:3 to form a uniformly dispersed slurry, the slurry is evenly coated on the surface of the current collector copper foil, and then transferred to a vacuum drying oven for complete drying to obtain a negative electrode sheet.
[0086] Preparation of electrolyte:
[0087] Ethylene carbonate (EC) and diethyl carbonate (DEC) are mixed at a volume ratio of 1:1, and then FEC (fluoroethylene carbonate) is added at a volume percentage of 5%. Then, the fully dried lithium salt LiPF6 is dissolved in a mixed organic solvent at a concentration ratio of 1 mol / L to prepare an electrolyte.
[0088] Preparation of isolation film: A PET / PP composite film with a thickness of 12 microns was selected.
[0089] Preparation of lithium-ion batteries:
[0090] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and the electrolyte is added, and a lithium-ion battery is assembled according to conventional processes.
[0091] Example 2
[0092] Different from Example 1, Figure 3 As shown, the surface of the composite foam aluminum layer 12 in the composite current collector 1 of the positive electrode of this embodiment is further provided with a carbon nano coating 13, and the thickness of the carbon nano coating 13 is 15 nm.
[0093] In addition, step 4) of the preparation method of the positive electrode plate also includes surface modification of the composite current collector 1 obtained after cooling, depositing a 15 nm thick carbon nanocoating 13, and hot rolling the surface modified composite current collector 1 on a precision rolling mill, with a rolling temperature of 120° C. and a rolling rate of 8%.
[0094] The rest is the same as in Example 1 and will not be described again here.
[0095] Example 3
[0096] Different from Example 1, in the composite current collector 1 of the positive electrode of this embodiment, the pore size d1 of the first foam aluminum 121, the pore size d2 of the second foam aluminum 122 and the pore size d3 of the third foam aluminum 123 satisfy the relationship: d1<d2<d3.
[0097] Specifically, in this embodiment, the pore size d1 of the first foam aluminum 121 is 4 μm, the pore size d2 of the second foam aluminum 122 is 8 μm, and the pore size d3 of the third foam aluminum 123 is 12 μm.
[0098] In addition, in step 1) of the preparation method of the positive electrode plate, in the first foam aluminum layer slurry, the particle size of the aluminum powder is 0.1 μm, and the particle size of the urea is 0.3 μm; in the second foam aluminum layer slurry, the particle size of the aluminum powder is 0.5 μm, and the particle size of the urea is 0.8 μm; in the third foam aluminum layer slurry, the particle size of the aluminum powder is 1 μm, and the particle size of the urea is 1.5 μm.
[0099] The rest is the same as in Example 1 and will not be described again here.
[0100] Example 4
[0101] Different from Example 1, the positive electrode active material coating 2 of the positive electrode of this embodiment includes positive electrode active material lithium nickel cobalt manganese oxide, conductive agent conductive carbon black, binder polyvinylidene fluoride and 1,3,5-tri(4-carboxyphenyl)benzene, wherein the mass ratio of lithium nickel cobalt manganese oxide, conductive carbon black, polyvinylidene fluoride and 1,3,5-tri(4-carboxyphenyl)benzene is 95:2:2:1.
[0102] The rest is the same as in Example 1 and will not be described again here.
[0103] Comparative Example 1
[0104] Different from Example 1, the positive electrode current collector of this comparative example adopts an aluminum foil current collector with a thickness of 10 μm.
[0105] The rest is the same as in Example 1 and will not be described again here.
[0106] Comparative Example 2
[0107] Different from Example 1, the current collector of the positive electrode of this comparative example adopts a single-layer foam aluminum current collector, and the foam aluminum current collector has a density of 0.5 g / cm³, a porosity of 90%, and a thickness of 10 μm.
[0108] The rest is the same as in Example 1 and will not be described again here.
[0109] The positive electrode sheets of the above embodiments and comparative examples were tested for ductility, stability and contact resistance, and the lithium-ion batteries made from the positive electrode sheets were tested for energy density and 1000-cycle room temperature cycle performance. The test results are shown in Table 1.
[0110] Ductility test: Under the same pressure (20 tons), the positive electrode sheets prepared in the embodiment and the comparative example were rolled to observe whether there was brittle fracture or cracking on the surface of the sheet. If any of the above phenomena occurred, it means that the ductility is poor.
[0111] Stability test: 10 positive electrode sheets prepared in the embodiments and comparative examples were respectively subjected to 90-degree folding and twisting experiments to observe the condition of the active materials at the folded or twisted parts. If any active materials fell off or broke, it indicated that the structural stability was poor.
[0112] Table 1
[0113] It can be seen from the test results in Table 1 that compared with the positive electrode prepared by the existing copper foil current collector or the single-layer foam aluminum current collector, the positive electrode of the present invention has better ductility, structural stability and lower contact resistance, because the positive electrode active material of the present invention has been infiltrated into the three-dimensional structure of the composite foam aluminum, and the gradient density composite foam aluminum itself has good flexibility, so it has a better retention effect on the active material infiltrated therein, thereby ensuring that the positive electrode prepared by the composite foam aluminum has better deformation resistance and structural stability during the processing process and the use of the battery, and can effectively prevent the positive electrode from brittle fracture or cracking, and effectively reduce the contact resistance, so the lithium ion battery prepared by the positive electrode of the present invention has higher energy density and cycle performance.
[0114] By comparing Example 1 and Example 2, it can be seen that when the surface of the composite foam aluminum layer of the positive electrode is further provided with a carbon nanocoating for surface modification, and the surface-modified composite current collector is further subjected to hot rolling treatment, the conductivity of the pole piece can be further improved, the interface resistance can be reduced, and it is beneficial to further improve the rate performance and cycle performance of the battery.
[0115] By comparing Example 1 and Example 3, it can be seen that when the composite foam aluminum layer of the positive electrode adopts a pore size gradient distribution, a multi-level porous structure that is beneficial to the diffusion of lithium ions and the embedding of active substances can be formed. The large pore size of the outer layer is beneficial to the rapid transmission of electrolyte and lithium ions, and the small pore size of the inner layer can inhibit the volume expansion of the active substance and maintain the stability of the electrode structure. It can ensure that the positive electrode has a high specific surface area and high conductivity while taking into account better mechanical strength and structural stability, further improving the energy density and cycle performance of the battery.
[0116] By comparing Example 1 and Example 4, it can be seen that when 1,3,5-tri(4-carboxyphenyl)benzene is further added to the positive electrode active material coating of the positive electrode, the deformation resistance and structural stability of the positive electrode can be further improved, while reducing the contact resistance of the pole piece and improving the cycle performance of the battery. This is because 1,3,5-tri(4-carboxyphenyl)benzene can form coordination bonds with the active material in the pores of the foamed aluminum to achieve the connectivity of the internal structure, which is beneficial to the improvement of the conductive performance, and can also enhance the internal support structure of the foamed aluminum and the anti-bending performance of the positive electrode sheet. At the same time, the binding effect of 1,3,5-tri(4-carboxyphenyl)benzene on the active material can also reduce the generation of free active materials during the use of the battery and improve the battery cycle performance.
[0117] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0118] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A high energy density lithium ion battery positive electrode, characterized in that: The composite current collector comprises a positive electrode active material coating coated on at least one surface of the composite current collector, wherein the composite current collector comprises an aluminum foil layer and a composite foam aluminum layer disposed on the aluminum foil layer, wherein the composite foam aluminum layer comprises three layers of foam aluminum with different densities, different porosities and different thicknesses; The composite foam aluminum layer includes a first foam aluminum, a second foam aluminum and a third foam aluminum which are arranged in sequence from the inside to the outside, and the density ρ1 of the first foam aluminum, the density ρ2 of the second foam aluminum and the density ρ3 of the third foam aluminum satisfy the relationship: ρ1>ρ2>ρ3; the porosity φ1 of the first foam aluminum, the porosity φ2 of the second foam aluminum and the porosity φ3 of the third foam aluminum satisfy the relationship: φ1<φ2<φ3; and the thickness h1 of the first foam aluminum, the thickness h2 of the second foam aluminum and the thickness h3 of the third foam aluminum satisfy the relationship: h1<h2<h3.
2. The high energy density lithium ion battery positive electrode according to claim 1, characterized in that: The density ρ1 of the first foam aluminum is 0.5-0.9 g / cm³, the density ρ2 of the second foam aluminum is 0.3-0.5 g / cm³, and the density ρ3 of the third foam aluminum is 0.1-0.3 g / cm³.
3. The high energy density lithium ion battery positive electrode according to claim 1, characterized in that: The porosity φ1 of the first foam aluminum is 50-70%, the porosity φ2 of the second foam aluminum is 70-85%, and the porosity φ3 of the third foam aluminum is 85-95%.
4. The high energy density lithium ion battery positive electrode according to claim 1, characterized in that: The thickness h1 of the first aluminum foam is 0.5-1 μm, the thickness h2 of the second aluminum foam is 1-2 μm, the thickness h3 of the third aluminum foam is 2-4 μm; the thickness h4 of the aluminum foil layer is 0.5-1 μm; and the total thickness of the composite current collector is 4-8 μm.
5. The high energy density lithium ion battery positive electrode according to claim 1, characterized in that: The surface of the composite foam aluminum layer is also provided with a carbon nano coating, and the thickness of the carbon nano coating is 10-20nm.
6. The high energy density lithium ion battery positive electrode according to claim 1, characterized in that: The pore size d1 of the first foam aluminum, the pore size d2 of the second foam aluminum, and the pore size d3 of the third foam aluminum satisfy the relationship: d1<d2<d3.
7. The high energy density lithium ion battery positive electrode according to claim 6, characterized in that: The pore size d1 of the first foam aluminum is 1-5 μm, the pore size d2 of the second foam aluminum is 5-10 μm, and the pore size d3 of the third foam aluminum is 10-15 μm.
8. A method for preparing a high energy density lithium ion battery positive electrode according to any one of claims 1 to 7, characterized in that: The following steps are involved: 1) preparing a first aluminum foam layer slurry, a second aluminum foam layer slurry and a third aluminum foam layer slurry respectively; The first foam aluminum layer slurry is made by mixing aluminum powder, urea and polyvinyl pyrrolidone in a mass ratio of 100:(15-25):1, adding anhydrous ethanol, and adjusting the solid content to 30-50wt%; The second foam aluminum layer slurry is made by mixing aluminum powder, urea and polyvinyl pyrrolidone in a mass ratio of 100:(25-35):1, adding anhydrous ethanol, and adjusting the solid content to 15-30wt%; The third foam aluminum layer slurry is made by mixing aluminum powder, urea and polyvinyl pyrrolidone in a mass ratio of 100: (45-55): 1, adding anhydrous ethanol, and adjusting the solid content to 5-15wt%; 2) preheating the aluminum foil substrate, and then coating the first aluminum foam layer slurry, the second aluminum foam layer slurry and the third aluminum foam layer slurry on the aluminum foil substrate in sequence, and spraying a small amount of anhydrous ethanol on the surface of each layer of slurry during the coating process; 3) Place the coated aluminum foil in a vacuum sintering furnace, and under the protection of argon or nitrogen, heat it to 650-750℃ at a heating rate of 2-5℃ / min, and keep it warm for 0.5-1h to sinter the aluminum powder to form a gradient porous structure. At the same time, urea decomposes to produce gas to form a gradient aluminum foam layer; 4) After cooling, the composite current collector is obtained, and the composite current collector is ultrasonically cleaned in anhydrous ethanol for 3-5 minutes to remove the urea decomposition products and impurities remaining on the surface, and then the composite current collector is dried; 5) coating the positive electrode active material coating slurry on at least one surface of the composite current collector and drying it to obtain the positive electrode of the lithium ion battery.
9. The method for preparing a positive electrode for a lithium-ion battery with a high energy density according to claim 8, characterized in that: Step 4) further includes surface modification of the composite current collector obtained after cooling, depositing a 10-20 nm thick carbon nanocoating, and hot rolling the surface modified composite current collector on a precision rolling mill at a rolling temperature of 100-150° C. and a rolling rate of 5-10%.
10. The method for preparing a positive electrode for a lithium-ion battery with a high energy density according to claim 8, characterized in that: In step 1), in the first aluminum foam layer slurry, the particle size of the aluminum powder is 0.1-0.4 μm, and the particle size of the urea is 0.2-0.5 μm; in the second aluminum foam layer slurry, the particle size of the aluminum powder is 0.2-0.8 μm, and the particle size of the urea is 0.4-1 μm; in the third aluminum foam layer slurry, the particle size of the aluminum powder is 0.5-1.5 μm, and the particle size of the urea is 0.8-1.8 μm.
Citation Information
Patent Citations
Preparation method of battery cell of lithium ion battery, lithium ion battery and application of lithium ion battery
CN113130844A
Composite current collector and preparation method thereof, electrode plate and secondary battery
CN114824160A
Negative pole piece, manufacturing method thereof, and secondary battery and electric device comprising negative pole piece
CN115832634A
High-energy-density multi-layer composite electrode, preparation method thereof and secondary battery
CN118522857A
Lithium secondary battery and manufacturiing methodtherefor
KR1020010029283A